Development of a Rotor-Mapping Algorithm to Locate Ablation Targets During Atrial Fibrillation - Ganesan, Prasanth (IEEE Life Sci Conf, 2018)
Catheter ablation therapy involving isolation of pulmonary veins (PVs) remains the cornerstone procedure to treat AF. However, due to the sub-optimal success rates of PV isolation, there is a need for new ablation techniques to locate AF ablation targets known as rotors, outside of the PVs. In this paper, we developed a novel rotor-mapping algorithm that uses a conventional diagnostic catheter, Lasso, to locate a rotor source. The algorithm, called the Region of Rotor (ROR) Mapping, utilizes the characteristics of local bipolar electrograms to navigate the catheter’s iterative placements while generating a map, overlaid on the atrial anatomy, that displays the potential rotor region. We evaluated the developed ROR mapping algorithm using a 2D simulation of AF on a tissue with heterogeneous conduction properties. The results demonstrated a significant success rate of 93% in accurately locating the region of the rotor with a mean distance of 1.4mm from the ground truth trajectory. The algorithm could play a critical role in mapping non-PV AF ablation targets and improving the outcome of AF ablation.